ANALYSIS OF QUESTIONS BASED ON THE COGNITIVE DIMENSIONS OF THE TIMSS IN MATHEMATICS TEXTBOOK CURRICULUM 2013 CLASS VII - Husna Nadhilah; Asyril Asyril; Azainil Azainil (Faculty of Teacher Training and Education, Mulawarman University, 2021)
This study aims to analyze and describe the mathematics problem in the sevengrade mathematics textbook K-13 based cognitive domain of Trends in International Mathematics and Science Study (TIMSS). Questions analyzed include competency test at the end of the chapter. The basis of this study is Indonesia's achievements in the TIMSS show that students' abilities are low. The type of this study is a descriptive qualitative research. Data collection method used by documentation. Documentation guide is classified in to cognitive domain of TIMSS. Data analysis technique of this research is data reduction, data display, and conclusion drawing/verification. The results of this study shows that overall the questions in in the seventh graders mathematics textbook K-13 are not sufficient to train the level of students' thinking development in the cognitive dimension. The proportion of TIMSS cognitive dimensions in this book is uneven. This is indicated by the difference in the proportion of each domain. The domain that dominates the TIMSS cognitive proportion dimension is the domain that applies and knows the domain, and domain reasoning still has a very small proportion. This shows that questions within these textbooks are still lacking in improving logic and critical thinking skills and reasoning skills to create new problem-solving solutions. However, this book has provided questions to encourage and encourage students' thinking skills on domain knowledge and domain application.